Perceived and actual option values of college enrollment - Yifan Gong; Todd R. Stinebrickner; Ralph Stinebrickner (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2020)
An important feature of post-secondary schooling is the experimentation that accompanies sequential decision-making. Specifically, by entering college, a student gains the option to decide at a future time whether it is optimal to remain in college or to drop out, after resolving uncertainty that existed at entrance about factors that affect the return to college. This paper uses data from the Berea Panel Study to quantify the value of this option. The unique nature of the data allows us to make a distinction between "actual" option values and "perceived" option values and to examine the accuracy of students' perceptions. We find that the average perceived option value is 65% smaller than the average actual option value (8,670 versus 25,040). A further investigation suggests that this understatement is not due to misperceptions about how much uncertainty is resolved during college, but, rather, because of overoptimism at entrance about the returns to college. In terms of policy implications related to college entrance, we do not find evidence that students understate the overall value of college, which depends on the sum of the option value and expectations at entrance about the returns to college.
Keywords: I21; I26; J24; D83; D84; 330; College Education; Dropout; Option Value; Learning Model; Expectations Data